T-cell immunity against senescence: potential role and perspectives - Matveeva, Kseniia; Vasilieva, Mariia; Minskaia, Ekaterina; Rybtsov, Stanislav; Shevyrev, Daniil (Frontiers in Immunology, 2024)
The development of age-associated diseases is related to the accumulation of senescent cells in the body. These are old non-functional cells with impaired metabolism, which are unable to divide. Such cells are also resistant to programmed cell death and prone to spontaneous production of some inflammatory factors. The accumulation of senescent cells is related to the age-associated dysfunction of organs and tissues as well as chronic inflammation that enhances with age. In the young organism, senescent cells are removed with the innate immunity system. However, the efficiency of this process decreases with age. Nowadays, more and more evidences are accumulating to support the involvement of specific immunity and T-lymphocytes in the fight against senescent cells. It has great physiological importance since the efficient elimination of senescent cells requires a high diversity of antigen-recognizing receptors to cover the entire spectrum of senescent-associated antigens with high precision and specificity. Developing the approaches of T-cell immunity stimulation to generate or amplify a physiological immune response against senescent cells can provide new perspectives to extend active longevity. In this mini-review, the authors summarize the current understanding of the role of T-cell immunity in the fight against senescent cells and discuss the prospects of stimulating adaptive immunity for combating the accumulation of senescent cells that occurs with age.